Analisis Perbandingan Antara Saham Syariah Dan Emas Ditinjau Dari Risk Dan Return Periode 2023 – 2025 - Sitorus, Sry Rahayu Ningsih; Hasibuan, Reni Ria Armayani; Harahap, Muhammad Ikhsan (Jambura Economic Education Journal, 2026)
This study aims to compare the investment performance of sharia stocks and ANTAM gold based on return and risk levels during the 2023–2025 period. The methodology used is a quantitative approach with a descriptive-comparative research model. The research data consists of the weekly closing prices of sharia stocks included in the Indonesia Sharia Stock Index, namely AALI, ACES, and ABMM, as well as the price of ANTAM gold. Data processing was conducted by calculating returns and risk using standard deviation, followed by the Jarque–Bera normality test, the Augmented Dickey–Fuller (ADF) stationarity test, the independent samples t-test, and volatility analysis using the GARCH (1,1) model. The results of the study indicate that there is no significant difference in return levels between sharia stocks and ANTAM gold. However, sharia stocks have higher risk and volatility levels compared to gold. These findings indicate that gold tends to be more stable as a hedging instrument, while sharia stocks offer greater return potential with the consequence of higher risk. The results of this study recommend portfolio diversification between sharia stocks and gold, and can serve as a reference for regulators. Further research is suggested to expand the study period and variables.